Dual Filler Effect of Compatibilized Pure and Oil Extended Ethylene Propylene Diene Monomer Nanocomposites - Rajasekar, R.; Das, C.K.; Nayak, G.C.; Ramakrishnan, S.; Harikrishnakumar, M.; Muthukumar, P. (Journal of Research Updates in Polymer Science, 2013)
Pure and oil extended ethylene propylene diene monomer nanocomposites were prepared using suitable compatibilizer. Since ethylene propylene diene monomer (EPDM) is non-polar, incorporation of organically modified nanoclay may not lead to better dispersion in the rubber matrix. Hence a polar rubber like epoxidized natural rubber (ENR) can be used as a compatibilizer for dispersing nanoclay in the EPDM matrix. ENR - organically modified nanoclay composites (EC) were prepared by solution mixing. The nanoclay used in this study is Cloisite 20A. ENR-nanoclay composites were incorporated in EPDM and oil-extended EPDM (OE-EPDM) matrices along with carbon black. The morphological studies prove that the nanoclay platelets get intercalated in ENR. Low loading of EC in EPDM and OE-EPDM matrices enhances the dispersion of nanoclay forming partially exfoliated platelets. Curing study shows improvement in torque and faster cure time for the compatibilized EPDM and OE-EPDM nanocomposites containing dual filler system compared to pure and single filler (carbon black) containing rubber compounds. Dynamic mechanical thermal analysis shows high storage modulus and lesser damping characteristics for the dual fillers containing EPDM and OE-EPDM compounds. The same compounds show tremendous improvement in mechanical properties. Scanning electron microscopic (SEM) images of tensile fractured single and dual filler containing rubber specimens show rough and tortuous path of fracture, which may be due to physical interaction between filler and rubber.